(untitled) (مجلة العلوم الشاملة, 2025)
Heavy metal pollution is considered one of the most important types of chemical pollution in addition to being one of the major problems of the age due to the accumulation of these elements in different natural environmental systems, which leads to many health problems. The aim of the present study is to investigate the heavy metals (As, Ba, Cd, Cr, Cu, Fe, Mn, Ni, Pb, Sr, Zn) accumulated in both the stems and leaves of the rosemary plant in two different geographical areas (Qasr Bin Ghasheer and Gharyan), where (leaves and stems) are considered a vital monitor through which the rate of metal pollution is detected. This is done by determining the ability of these heavy metals to accumulate in the rosemary plant and comparing them with the internationally permitted limits. Through this study, the results showed that most of the concentrations of heavy elements in (Gharyan sample) whether in the leaves or stems fall within the internationally permitted limit except for element (Ba, Cu, Sr) which was found higher than the permitted range. As for the results obtained for the rosemary sample in the (Qasr Bin Ghasheer) area, they were within the permissible limit only with the exception of the two elements (Sr, Ba ) was higher than the internationally permissible limit whether in the leaves or stems of rosemary. Based on that, we therefor believe that rosemary plant is one of the most significant method to determine the amount of the pollution which is related to the heavy metals.